Treatment of the rectocele caused by pelvic floor muscles incompetence in women - A. O. Solovyov; A. A. Vorobyev; O. L. Solovyev; G. A. Solovyova; E. V. Litvina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To evaluate the results of surgical treatment of obstructed defecation syndrome caused by rectocele due to posterior vaginal wall prolapse by original reconstruction method of perineal muscles. Material and methods. Original method of sphincter plication and levatorplasty was approved at surgical treatment of obstructed defecation syndrome due to pelvic floor muscles incompetence in 134 patients. Results. Defecation function in studied group of patients was evaluated by Wexner constipation score. Prior to the surgery the average score was 23.5±4.1, after operation - 12.4±2.2, in 1 month after operation it decreased to 5.8±1.9, difference in score in comparison to preoperative level was statistically significant (р